2003
DOI: 10.1159/000072157
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Teachers’ Voice Quality during a Working Day with and without Electric Sound Amplification

Abstract: The present study investigated changes in the voice quality of teachers during a working day (a) in ordinary conditions and (b) when using electrical sound amplification while teaching. Classroom speech of 5 teachers was recorded with a portable DAT recorder and a head-mounted microphone during the first and the last lesson of a hard working day first in ordinary conditions and the following week using amplification. Long-term average spectrum and sound pressure level (SPL) analyses were made. The subjects’ co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 26 publications
2
29
0
8
Order By: Relevance
“…With regard to the point of view of the children, most of the teachers in the study reported that children became immediately used to the novelty, and they also benefitted from listening. Also this aspect is in agreement with some previous reports indicating that poor voice quality in teachers reduces the intelligibility of speech [14,15,24,25], while amplification both reduces the need for repetition and permits better concentration [15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…With regard to the point of view of the children, most of the teachers in the study reported that children became immediately used to the novelty, and they also benefitted from listening. Also this aspect is in agreement with some previous reports indicating that poor voice quality in teachers reduces the intelligibility of speech [14,15,24,25], while amplification both reduces the need for repetition and permits better concentration [15].…”
Section: Discussionsupporting
confidence: 93%
“…In the first years of this decade, a few studies demonstrated that portable systems permit up to 6.0 dB SPL reduction of the voice intensity during a simulated classroom lecture [12][13][14]. Furthermore, among a group of 33 teachers, 97% reported easier voice production and 82% found improved vocal endurance [15]. More recently, the vocal portable dosimeters (KayPENTAX Ambulatory Phonation Monitor) permit a more reliable monitoring of vocal dose in an occupational setting.…”
Section: Methodsmentioning
confidence: 99%
“…Irregularity seems to be a sensitive indicator of voice quality [21]. This result are similar to the results of the study of Jónsdottir [24] who reported better voice quality in teachers with vocal loading when using electric sound amplification.…”
Section: Kob Et Al: Influence Of Room Acoustics On the Teacher's supporting
confidence: 87%
“…Some studies found a lowered SPL in teachers with less vocal loading (e.g. [22,24]), but these studies investigated the influence of sound amplification during a longer teaching period.…”
Section: Kob Et Al: Influence Of Room Acoustics On the Teacher's mentioning
confidence: 99%
“…Within the several possibilities of spectrographic analysis, the Long-term average spectrum (LTAS) offers the possibility of quantifying the quality of a voice, pointing the differences between gender, age, professional voices -talked and sang -and dysphonic voices (Leino, 1993;Mendoza et al, 1996;Navarro, 2000;Barrichelo et al, 2001;Hartl et al, 2001;Linville & Rens, 2001;Bele, 2002;Camargo, 2002;Sjölander, 2003;Jónsdottir et al, 2003;Hartl at al., 2003;Laukkanen et al, 2004;Camargo et al, 2004;Pinczower & Oates, 2005;Soyama et al, 2005).…”
Section: Introductionmentioning
confidence: 99%